Survival and Incidence Patterns of Pancreatic Neuroendocrine Tumors Over the Last 2 Decades: A SEER Database Analysis - Sonbol, Mohamad Bassam; Mazza, Gina L; Mi, Lanyu; Oliver, Thomas; Starr, Jason; Gudmundsdottir, Hallbera; Cleary, Sean P; Hobday, Timothy; Halfdanarson, Thorvardur R (The Oncologist, 2022)
Abstract Background Pancreatic neuroendocrine tumors (pNETs) are rare cancers with outcomes determined by multiple factors including grade, stage, and clinical presentation. In this study, we aimed to determine the prognosis of patients with pNETs using a large population-based database. Materials and Methods In this population-based study, we identified patients with pNETs from the SEER 18 registry (2000-2016) using a combination of ICD-O-3 and histology codes. We calculated age-adjusted incidence rates using SEER*Stat 8.3.5. In addition, we analyzed overall survival (OS) using the Kaplan-Meier method, and investigated prognostic factors using a multivariable Cox proportional hazards model. Results A total of 8944 pNETs patients were identified. Annual incidence rates increased from 0.27 to 1.00 per 100 000. This was largely explained by an increase in number of patients diagnosed with localized disease in more recent years (2012-2016). Median OS was 68 months (95% CI [64, 73]) and 5-year OS rates in localized, regional, and metastatic disease were 83%, 67%, and 28%, respectively. There was a significant improvement in OS for patients diagnosed between 2009 and 2016 (median OS 85 months) compared with those diagnosed between 2000 and 2008 (median OS 46 months) (HR 0.66; 95% CI [0.62, 0.70]). This improvement in OS was consistent across all stages. Conclusions and Relevance This study shows a steady increase pNETs incidence with notable stage migration to earlier stages in recent years. This increase in incidence is accompanied by a significant improvement in survival across different disease stages. This study used the SEER cancer registry to research trends in the incidence and mortality rates of pancreatic neuroendocrine tumors in the United States over the past 2 decades.